Efektivitas Ekstrak Etanol Bunga Telang (Clitoria Ternatea L ) sebagai Nefroprotektor terhadap Tikus Putih Jantan (Rattus Norvegicus) yang Diinduksi Gentamisin - Rien Sapitri Br Sihaloho; Asyrun Alkhairi Lubis; Novitaria Br Sembiring (Lembaga Pengembangan Kinerja Dosen, 2025)
Nephrotoxicity is a disorder of kidney function that can occur due to exposure to drugs, environmental chemicals, or other toxic substances. One aminoglycoside antibiotic known to have nephrotoxic effects is gentamicin, which is often used in the treatment of bacterial infections, but can cause kidney damage if used in high doses or for long periods. Therefore, it is important to find agents that can protect the kidneys from the side effects of this drug. Butterfly Pea Flower (Clitoria ternatea L.) is a plant known to contain secondary metabolites with antioxidant activity that have the potential to act as nephroprotective agents. These compounds can help combat oxidative stress that occurs in the kidneys due to exposure to toxic substances. This study aims to determine the optimal dose of Butterfly Pea Flower ethanol extract in protecting the kidneys of white rats from gentamicin-induced damage. A total of 25 male white mice were divided into five treatment groups: a normal control group (given distilled water), a negative control group (given only gentamicin 100 mg/kgBW), and three test groups given Butterfly Pea Flower extract at doses of 100, 200, and 400 mg/kgBW. Evaluation was carried out by measuring serum creatinine levels as an indicator of kidney function and histopathological analysis of kidney tissue to assess structural damage to the rats' kidneys. The results showed that administration of gentamicin caused a significant increase in serum creatinine levels and relative kidney weight, indicating acute kidney damage. Conversely, administration of Butterfly Pea Flower extract, especially at a dose of 400 mg/kgBW, provided the most effective protection against kidney damage. This was indicated by a decrease in creatinine levels approaching normal control values and improvement in histological damage to kidney tissue, such as repair of the structure of kidney tubules damaged by the effects of gentamicin.